Fractal form PEDOT/Au assemblies as thin-film neural interface materials. (4th June 2018) - Krukiewicz, Katarzyna; Chudy, Magdalena; Vallejo-Giraldo, Catalina; Skorupa, Małgorzata; Więcławska, Daria; Turczyn, Roman; Biggs, Manus
Abstract: Electrically conducting polymer formulations have emerged as promising approaches for the development of interfaces and scaffolds in neural engineering, facilitating the development of physicochemically modified constructs capable of cell stimulation through electrical and ionic charge transfer. In particular, topographically functionalized or neuromorphic materials are able to guide the growth of axons and promote enhanced interfacing with neuroelectrodes in vitro . In this study, we present a novel method for the formation of conducting polymer/gold assemblies via a combinational sputter and spin coating technique. The resulting multilayered PEDOT/Au substrates possessed enhanced electrochemical properties as a function of the number of deposited organic/inorganic layers. It was observed that through subsequent electrochemical conditioning it was possible to form neuromorphic fractal-like assemblies of gold particles, which significantly impacted on the electrochemical characteristics of the PEDOT/Au films. PEDOT/Au assemblies were observed to possess unique topographical features, advantageous charge storage capacity (34.9 ± 2.6 mC cm −2 ) and low electrical impedance (30 ± 2 Ω at 1 kHz). Furthermore, PEDOT/Au assemblies were observed to facilitate the outgrowth of neurites in a mixed ventral mesencephalon cell population and promotean increase in the neurons/astrocytes ratio relative to all experimental groups, indicating PEDOT/Au biomimetic neuromorphic assemblies as promising materials in engineering electrically conductive neural interface systems.